PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF ONLINE MENGGUNAKAN SCHOOLOGY BERBANTUAN WEB DESMOS MATERI GRAFIK FUNGSI KUADRAT - Nisyak, Robiatun; Trapsilasiwi, Dinawati; Fatahillah, Arif; Susanto, S; Murtikusuma, Randi Pratama (Kadikma, 2018)
Abstract. This research aims to develop an online interactive learning media use assisted Schoology Desmos web for quadratic function graph. This is the kind of research the research development. The process of developing this learning media by using a customized Thiagarajan model or 4-D model. This development model consists of four stages, namely define, design, develop and disseminate. Trial subject of this research is students of class XI IPA 3 at SMAN Jenggawah with a total of 33 students. The results of the learning media validation in the valid criteria with a correlation coefficient of 0.94 including the "Very High" category. The practical level is seen from user response questionnaire obtained 83,5% including the “Very Good” category. While the effectiveness level is based on the learning test result obtained 81,82% of 33 students scored above the KKM. Based on the results of the data analysis, the results can be obtained that the online interactive learning media use assisted Schoology Desmos web for quadratic function graph has met valid, practical, and effective criteria. Keywords: Development, Media, Schoology, Web Desmos, Quadratic Function Graph.